PROSEDUR PELAYANAN PADA BIRO PERJALANAN WISATA SURYA AGUNG TOUR DALAM MENINGKATKAN KEPUASAN KONSUMEN - , IKA KUNTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It can not disavow that people activities which preoccupied by their job and education make them feel bored and need time to travelling. But now, almost all people do not want to take a risk with dealings for accommodation, transportation, and tourism object ticket. People submit all of dealings to travel agent with expectation they will get excellent service and satisfaction. Travel agent is a tourism industry which engages in service. Customer can not feel it before they buy and travelling. On behalf of it, Surya Agung Tour has commitment to always strive to give service excellent for its customer. On that basic, the researcher wants to watch closely and research how a Surya Agung Tour serves its customer appropriate Standard Operational Procedure, what its problems within give serviceand how to solve its problems. The goals of this research are to know customer satisfaction level concerning service which has given by Surya Agung Tour and to know its problems. The researcher used qualitative method based on participation in every activity in Surya Agung Tour. The researcher also used questioner which has made to diagram pie, so the researcher knows customer satisfaction level concerning service which has given. The result of this research, can conclude that service has given by a travel agent with its relation has influence to customer satisfaction level. If only travel agent who give the best service but its relation did not give its best service, so customer will not satisfied.